Fruit and seed traits of Berberis croatica Horvat and Berberis vulgaris L. - Karlovic, Ksenija; Kremer, Dario; Jurisic Grubjesic, Renata; Popovic, Zvjezdana (Acta Botanica Croatica, 2012)
The three year variability of fruits and seeds was investigated in Berberis croatica (Vošac, Mt Biokovo, Rakov Potok near Zagreb) and in B. vulgaris (Fran Kušan Pharmaceutical Botanical Garden in Zagreb). Berberis croatica had the following dimensions of fruits (seeds): length 7.28–7.88 (4.57–5.03) mm; width 3.85–3.99 (width 1:2.06–2.20; width 2: 1.44–1.63) mm; weight 0.065–0.078 (0.0116–0.0134) g. Dimensions of B. vulgaris fruits (seeds) were: length 10.20–11.29 (5.71–6.24) mm; width 5.29–5.83 (width 1: 2.40–2.71; width 2: 1.60–1.98) mm; weight 0.1602–0.2199 (0.0146–0.0235) g.The fruit shape of both species was similar and the length/width ratio was 1.91–2.04 in B. croatica and 1.77–2.07 in B. vulgaris. The number of seeds per fruit was 1.23–1.58 in B. croatica and 1.36–1.54 in B. vulgaris. Generally, fruits and seeds of B. vulgaris were significantly longer, wider and heavier than fruits and seeds of B. croatica. ANOVA showed significant statistical differences between populations for all analyzed fruit and seed traits while the species significantly differed in all traits, except in the fruit shape and number of seeds in fruit.